Influence of BCZT Dopant on Dielectric Properties of PZT Ceramics - Pichitchai Butnoi (2018)
© 2015 Taylor & Francis Group, LLC. (1-x)Pb(Zr 0.52 Ti 0.48 O 3 [PZT] - x(Ba 0.9 Ca 0.1 )(Ti 0.85 Zr 0.15 )O 3 [BCZT] (x = 0, 0.04, 0.08, 0.10, 0.20 and 0.30) were prepared by a two-step mixed-oxide method. XRD patterns of all ceramic samples exhibited a complete perovskite phase without impurity phase and no a second phase. The dielectric studies indicated that the phase transition behavior of the ceramic compositions becomes more diffuse with increasing BCZT contents. Moreover, The maximum dielectric constant and the transition temperature decrease with the increasing BCZT contents. The addition of BCZT contents ca used the decrease of the tanδ value for 218% compared to that of pure PZT.